Design of porphyrin-based conjugated microporous polymers with enhanced singlet oxygen productivity. Issue 50 (4th May 2016) - Hynek, Jan; Rathouský, Jiří; Demel, Jan; Lang, Kamil
Abstract : Novel porphyrin-based conjugated microporous polymers displayed high O2 ( 1 Δg ) production, were stable in organic solvents, and did not undergo measurable photobleaching. Abstract : Novel non-toxic materials with antimicrobial surfaces are needed for medicinal applications. Potential alternatives for bacterial inactivation include materials that produce singlet oxygen, O2 ( 1 Δg ), a short-lived, highly oxidative, and cytotoxic species. We synthesized a promising group of materials, porphyrin-based conjugated microporous polymers (CMPs), which effectively generate O2 ( 1 Δg ) under visible light irradiation. CMPs were rationally designed and synthesized to maximize O2 ( 1 Δg ) production. A strategy based on three-dimensional frameworks allowed the immediate environment of the porphyrin units to be tuned and their structure–property relationships to be elucidated. We investigated the photophysical and photochemical properties of the frameworks and compared them with the properties of porphyrin-based CMPs and metal–organic frameworks. In general, the O2 ( 1 Δg ) production activity of the CMPs correlated with neither the surface area nor with the pore volume. The novel CMPs displayed high O2 ( 1 Δg ) production, were stable in organic solvents, and did not undergo measurable photobleaching.